2015
DOI: 10.1007/s10600-015-1394-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Pyrrole Alkaloid from Leccinum Extremiorientale

Abstract: Leccinum extremiorientale for the first time. Their structures were identified on the basis of 1D and 2D NMR spectroscopy as well as MS.Keywords: Leccinum extremiorientale, pyrrole alkaloids, 2-[2-formyl-5-(methoxymethyl)-1H-pyrrol-1-yl] acetic acid.Leccinum extremiorientale belongs to the higher fungus of the genus Leccinum in the family Boletaceae and grows worldwide, especially in the northern temperate zone. It is distributed mainly in Sichuan, Hubei, Yunnan, Guizhou, Guangxi, Tibet, and other places of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In contrast, compounds I and III were reported as active ingredients in the fruits of Lycium chinense [ 8 ] and Morus alba [ 11 ] that have hepatoprotective and macrophage activation functions, respectively. Compound I is also found in mushrooms such as Leccinum extremiorientale [ 12 ] and Inonotus obliquus [ 13 ]. Recently, the same types of pyrrole alkaloid derivatives have been isolated from the fruiting bodies of another edible mushroom Phlebopus portentosus [ 14 ], and it has been reported that they significantly attenuated H 2 O 2 -induced cell damage in human neuroblastoma SH-SY5Y cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, compounds I and III were reported as active ingredients in the fruits of Lycium chinense [ 8 ] and Morus alba [ 11 ] that have hepatoprotective and macrophage activation functions, respectively. Compound I is also found in mushrooms such as Leccinum extremiorientale [ 12 ] and Inonotus obliquus [ 13 ]. Recently, the same types of pyrrole alkaloid derivatives have been isolated from the fruiting bodies of another edible mushroom Phlebopus portentosus [ 14 ], and it has been reported that they significantly attenuated H 2 O 2 -induced cell damage in human neuroblastoma SH-SY5Y cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…4-(2-Formyl-5-(hydroxymethyl)-1H-pyrrol-1-yl)butanoic acid (PBA) (65) was rst isolated from kako-bushi-matsu, a thermally processed Aconitum japonicum root product used in oriental medicine for its analgesic, diuretic and cardiac effects. 58 PBA (65) has been isolated no fewer than eleven times, [4][5][6][7]34,41,[58][59][60][61][62] and its methyl ether 66 no fewer than eight, [6][7][8]34,38,46,63,64 from both plant and fungal sources. The yield of PBA (65) from kako-bushi-matsu, which is prepared by autoclaving Aconitum roots at 110 C, was determined to be 10-fold greater than the yield of PBA (65) from Aconitum roots dried at 50-55 C. 58 This observation is consistent with the proposal that PBA is the product of Maillardtype reactions.…”
Section: -Formylpyrroles Derived From Biogenic Aminesmentioning
confidence: 99%
“…Due to a wide variety of secondary metabolites from fungus and their biological activities, extensive attention has been paid to the researches of fungus both in China and abroad [2]. Boletus is popular because of its delicious taste, appreciated nutrition value [3], and a variety of medicinal effects [4]. e chemical composition of the Boletus was mainly terpenes, flavonoid [5], phenols [6], and alkaloids, which possessed comprehensive biological activities, such as antioxidant, antifatigue, antitumor, and anti-inflammatory [7,8].…”
Section: Introductionmentioning
confidence: 99%